2015
DOI: 10.3748/wjg.v21.i14.4323
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate antigen 19-9 for differential diagnosis of pancreatic carcinoma and chronic pancreatitis

Abstract: Elevated CA19-9 by itself is insufficient for differentiating pancreatic carcinoma and chronic pancreatitis, however, it increases suspicion of pancreatic carcinoma and may complement other clinical findings to improve diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 54 publications
0
39
0
1
Order By: Relevance
“…We observed that CA19.9, which has been widely investigated in pancreatic illness ( Winter et al , 2013 ), was also the most relevant marker for PA diagnosis, with a sensitivity of 79% and specificity of 93%. Two meta-analyses found similar values, with 79–81% sensitivity and 82–90% specificity ( Ballehaninna and Chamberlain, 2012 ; Su et al , 2015 ). However, the usefulness of CA19.9 for PA diagnosis is still debated because of its low specificity.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We observed that CA19.9, which has been widely investigated in pancreatic illness ( Winter et al , 2013 ), was also the most relevant marker for PA diagnosis, with a sensitivity of 79% and specificity of 93%. Two meta-analyses found similar values, with 79–81% sensitivity and 82–90% specificity ( Ballehaninna and Chamberlain, 2012 ; Su et al , 2015 ). However, the usefulness of CA19.9 for PA diagnosis is still debated because of its low specificity.…”
Section: Discussionmentioning
confidence: 74%
“…To date, the carbohydrate antigen CA19.9 (CA19.9), which has been approved by the FDA for PA management, is the only marker used in daily practice. Its clinical interest has been intensively studied, and it has a sensitivity of 70–81% for PA diagnosis ( Chan et al , 2014 ; Su et al , 2015 ). The well-known limitation of CA19.9 is its low specificity due to the presence of elevated levels in non-malignant situations, such as cholestasis or diabetes mellitus.…”
mentioning
confidence: 99%
“…PC is an aggressive disease with almost no symptoms until the cancer is well established [24,25]. Carbohydrate antigen 19 − 9 is the only diagnostic marker approved by the FDA, but its diagnostic potential is limited due to its limited sensitivity and speci city [26,27]. Therefore, screening new tumor biomarkers is important for the early diagnosis and targeted treatment of PC.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient demonstrated repeatedly negative biopsy by EUS. Furthermore, CA 19-9 was normal throughout the evaluation, though it is elevated in 80% of cases of pancreatic adenocarcinoma, especially cases presenting with common bile duct obstruction [ 14 , 15 ]. Our patient did not have Lewis null blood type, which does not produce CA 19-9 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%